Applying social influence insights to encourage climate resilient domestic water behavior: Bridging the theory‐practice gap. (14th December 2018) - Lede, Ellin; Meleady, Rose
Abstract : Water scarcity is one of the most pressing issues of our time and it is projected to increase as global demand surges and climate change limits fresh water availability. If we are to reduce water demand, it is essential that we draw on every tool in the box, including one that is underestimated and underutilized: social influence. Research from the psychological sciences demonstrates that behavior is strongly influenced by the behavior of others, and that social influence can be harnessed to develop cost‐effective strategies to encourage climate resilient behavior. Far less attention has been paid to investigate water‐related interventions in comparison to interventions surrounding energy. In this paper, we consider the application of three social influence strategies to encourage water conservation: social norms ; social identity ; and socially comparative feedback. We not only review their empirical evidence base, but also offer an example of their application in the residential sector with the aim of highlighting how theoretical insights can be translated into practice. We argue that collaborations between researchers and industry are essential if we are to maximize the potential of behavior change interventions to encourage climate resilient water behavior. This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Behavior Change and Responses